Local urban cultural policies. Street art and graffiti in Vienna and Munich. - Spitzer, Thomas (Lang, 2018)
Different European cities lately recognized the cultural value of street art and graffiti by embedding them in the structures of their local cultural programs. This paper presents the results of case studies in Vienna and Munich and depicts the different approaches of local cultural policies concerning street art and graffiti used in both cities.
Keywords: Großstadt; Graffiti; Straßenkunst; Kulturpolitik; Städtevergleich; Streetart